Ramsay Hunt Syndrome: A Clinical Management Experience from a Secondary Care Public Hospital - Balasubramanian, Madhubala; Haridas, Indu Tharayappurath; Jeyaganeshamoorthi, B; Ponnusankar, Sivasankaran (Indian Journal of Pharmacy Practice)
Introduction: Ramsay Hunt Syndrome is a rare and severe infection caused by varizella zoster virus. Case: The present case describes the manifestations and treatment strategies followed for a 70- year-old woman who visited to a secondary care hospital, Udhagamandalam. The presence of facial palsy, bell’s palsy, difficulty in closing the eyes, otalgia and shingles confirmed Ramsay Hunt Syndrome. The early management with acyclovir and prednisolone had shown improvement in clinical outcome of the patient. However, as a preventive measure, it is essential to undergo immunization with varizella vaccine in elder people in this locality.
Keywords: Ramsay hunt syndrome; VZV; Facial palsy; Acyclovir; Management